In vitro evaluation of the antiviral activity of extracts from the lichen parmelia perlata (L) Ach. Against three RNA viruses (2007)
"Substances extracted from lichens have previously been reported to possess antimicrobial activities against various groups of bacteria, fungi and viruses. Due to the high abundance of Parmelia perlata in the Eastern parts of Nigeria, we decided to explore whether it possesses antiviral activity against some common animal and human viruses. METHODOLOGY:The dried and powdered lichen was extracted with acetone, water and 4% (v/v) NaOH (to yield a crude polysaccharide fraction) using standard methods. The cytotoxicity of the extracts was investigated on HEP-2, Vero and L20 cell lines. The antiviral properties were determined against yellow fever, poliomyelitis and infectious bursal disease virus of chickens using the end-point cytopathic effect assay. Phytochemical evaluations of the extracts were also carried out. RESULTS:Phytochemical tests showed the presence of flavonoids, saponins, tannins, glycosides, steroidal aglycone, carbohydrates and also the presence, in trace amounts, of some oligodynamic elements. Cytotoxicity tests revealed that while L20 was susceptible to the extracts at a concentration of 50 microg/ml, the extracts were generally toxic to the cell lines at concentrations above 500 microg/ml. The order of sensitivity of the cell lines was L20 > HEP-2 > Vero. The water and acetone extracts showed no activity against the viruses when tested at concentrations below the cytotoxic level while the crude polysaccharide fraction showed activity against yellow fever virus with an IC50 of 15 microg/ml. The time of addition of the test extracts to the infected cells did not have significant effect on cytopathic effect inhibition. CONCLUSIONS:The results showed that the crude polysaccharide fraction from Parmelia perlata possesses specific antiviral activity against yellow fever virus. It is postulated that a major mechanism of inhibition of yellow fever infection by the crude polysaccharide fraction of the lichen could be by attack on the viral envelope."